Converting infiltration swales to sustainable urban drainage systems can improve water management and biodiversity - Helmreich, Brigitte; Deeb, Maha; Eben, Patrizia; Egerer, Monika; Kollmann, Johannes; Schulz, Stefanie; Pauleit, Stephan; Weisser, Wolfgang W.; Schloter, Michael (Frontiers in Environmental Science, 2025)
Sustainable Urban Drainage Systems (SUDS) are ecosystems that are based on engineered soil and designed plant communities to manage stormwater on-site and to enhance infiltration, evapotranspiration, and cooling, thus reducing flooding and urban heat islands. In addition, SUDS may act as hotspots for biodiversity and could be more socially accepted if they work well and are multifunctional. However, we still lack a critical understanding of the techno-ecological basis to construct SUDS sustainably. Due to climate change and pollutants such as de-icing salts, SUDS are confronted with harmful environmental triggers that interfere with their sustainable development. Thus, the challenge is to combine stormwater treatment and urban drainage with principles of restoration ecology, while implementing expertise from soil science, microbiome research, and plant ecology. In this perspective paper, we will discuss the SUDS development and maintenance principle and the role of interdisciplinary research in reaching these goals.